Preparation of a Poly (Hydroxamic Acid) Ion-Exchange Resin from Poly (Ethyl Acrylate-Divinyl Benzene) Beads and its Properties. - Wan Yunus, Wan Md Zin (1988)
A method to synthesize a poly (hydroxamic acid) chelating ion-exchange resin from poly (ethyl acrylate-divinyl benzene) and its behaviour towards some metal ions are described. The resin was prepared from this copolymer by treatment with hydroxylamine in the presence of sodium hydroxide. The hydroxamic acid capacity of the product is 2.29 mmol/g and its sorption rate, based on sorption of copper ion at pH 4, is rapid. Sorption capacities of Fe(/II), Cu, Co, Ni and Zn ions are pH dependent and its selectively towards these metal ions is in the following order: Fe(II/) >Cu >Ni >Co >Zn. The ability of this resin to extract and to separate these metal ions are also reported.